Integration and performance verification of FE/NCV process simulation software - Sriram Ramachandar. (2008)
In this thesis, already developed three-dimensional finite element / nodal control volume (FE / NCV) simulation procedures are first understood. Studies are performed to stream-line the sequence of data entry and to make it consistent for all the above processes. The purpose of the interface program is to combine the process of providing the input parameters for all the above mentioned manufacturing processes.